Tweeting to Learn: Understanding Twitter Through the Lens of Connectivism - Nirupama Akella (InSight : A Journal of Scholarly Teaching, 2014)
Twitter, primarily a social media outlet, has recently started foraying and gaining a foothold in higher education. Written from a student perspective, this paper attempts to explain and critically discuss the usage and popularity of Twitter as a tool of active learning in higher education. The author writes about her student experience of using Twitter in her Public Relations Communications graduate class. The paper explores and scrutinizes the social media channel within the theoretical framework of connectivism.